Divergent cardiac and renal effects of miR-181c-5p inhibition in a rodent heart failure model - Boen, Jente R. A.; Gevaert, Andreas B.; Dendooven, Amélie; Krüger, Dustin; Tubeeckx, Michiel; Van Fraeyenhove, Jens; Bruyns, Tine; Segers, Vincent F. M.; Van Craenenbroeck, Emeline M. (Frontiers in Cardiovascular Medicine, 2024)
Aims MiR-181c-5p overexpression associates with heart failure (HF) and cardiac damage, but the underlying pathophysiology remains unclear. This study investigated the effect of miR-181c-5p inhibition on cardiac function and fibrosis in a rodent model of diastolic dysfunction, and evaluated additional effects on kidney as relevant comorbid organ. Methods and results Diastolic dysfunction was induced in male C57/BL6J mice (n = 20) by combining high-fat diet, L-NG-nitroarginine methyl ester, and angiotensin II administration, and was compared to sham controls (n = 18). Mice were randomized to subcutaneous miR-181c-5p antagomiR (INH) or scrambled antagomiR injections (40 mg/kg/week). HF mice demonstrated diastolic dysfunction and increased fibrosis, which was attenuated by INH treatment. Remarkably, HF + INH animals had a threefold higher mortality rate (60%) compared to HF controls (20%). Histological examination revealed increased glomerular damage in all INH treated mice, and signs of thrombotic microangiopathy (TMA) in mice who died prematurely. Quantitative polymerase chain reaction demonstrated a miR-181c-5p-related downregulation of cardiac but not renal Tgfbr1 in HF + INH mice, while INH treatment reduced renal but not cardiac Vegfa expression in all mice. Conclusion This study demonstrates cardiac anti-fibrotic effects of miR-181c-5p inhibition in a rodent HF model through targeting of Tgfbr1 in the heart. Despite improved diastolic function, HF + INH mice had higher mortality due to increased predisposition for TMA, increased renal fibrosis and glomerular damage, associated with Vegfa downregulation in kidneys.